Sensing of pheromones from Euschistus heros (F.) stink bugs by nanosensors - Janine Martinazzo; Sandra C. Ballen; Juliana Steffens; Clarice Steffens (Sensors and Actuators Reports, 2022)
This revision covers the agriculture system, the losses due to insect pest, the pheromone definition and how they can be deployed. Specially, this work focus in pheromones from stink bug Euschistus heros. The use of different techniques for pest control in agriculture seeks safety and environmental preservation. The stink bug E. heros is one of the major pests that affects crops in Brazil. This insect releases pheromone to mate in low amounts. A promising and efficient alternative for the detection of this volatile compound is the use of nanosensors. This paper provides a review of the most recent works in nanosensors used for detection insect pheromones, including gas sensors with sensitive coatings in nanoscale. Also, other applications of gas nanosensors in pheromone detection in agriculture are described. Nanosensors are potential solutions for pest management and can contribute to developing innovative and technological solutions for agriculture.